El Monesti de Bellpuig, donat al CIM i a l'Ajuntament (Revista Bellpuig, 1998)
Keywords: bellpuig de artá

The ideology of reform and changing ideas concerning Jews in the works of Rupert of Deutz and Hermannus quondam Iudeus - Abulafia, Anna Sapir (Christians and Jews in Dispute: Disputational Literature and the Rise of Anti-Judaism in the West (c. 1000-1150), 1998)
Num Pages: xvi, 310 Pp.
Keywords: 👤 hermann of cologne

Vom Kloster zur Pfarrgemeinde: Zur Geschichte der katholischen Kirchengemeinde in Enkenbach - Ammerich, Hans (850 Jahre Kloster Enkenbach 1148-1998, 1998)
Keywords: enkenbach

Les "courts" de l'ordre de Prémontré au XlIe siècle. Formation et premiers développements - Bautier, Robert-Henri (Les Cahiers de Beauport, 1998)
Keywords: 📚 premonstratensian (general)

Ein wiedergefundener Bibliothekskatalog der Prämonstratenserabtei Weißenau (1604): seine Bearbeitung durch Charles-Louis Hugo - Binder, Helmut (Revue Mabillon, 1998)
Keywords: weissenau

Un inventaire de la bibliothèque de Fontcaude en 1352 - Bondéelle-Souchier, Anne (Analecta Praemonstratensia, 1998)
Keywords: fontcaude

Wer lebte und starb im ostfriesischen Kloster Barthe? - Burkhardt, Angelika (Archäologie in Niedersachsen, 1998)
Keywords: barthe

Le diable et la trinité tricéphales. A propos d'une pseudo- « vision de la Trinité » advenue à un novice de saint Norbert de Xanten - Bœspflug, François (Revue des Sciences Religieuses, 1998)
La Vita Norberti, rédigée vers le milieu du XIIe siècle, rapporte la vision qu'aurait eue un des premiers novices du saint fondateur de l'Ordre de Prémontré, celle d'un personnage à trois têtes prétendant être la Trinité. A cette date, pourtant, le motif tricéphale était réservé au diable, et la Trinité tricéphale ne prendra son essor dans l'art qu'un siècle plus tard, pour connaître à partir du XIVe un vif succès. L'article en montre les premiers exemples, présente diverses théories concernant la genèse de la Trinité tricéphale, et s'efforce d'analyser cette avance de l'histoire des visions sur l'histoire des types iconographiques. La « diabolisation » de la tricéphalie en milieu prémontré traduit peut-être la volonté de refouler toute trace résiduelle de culte celtique.
Keywords: 📚 premonstratensian (general)

Vorläufige Nachricht von der Grabung im Kloster "Hradisko" in Olmütz im Jahre 1996 - Cižmár, Zdenek; Kohoutek, Jirí (Sborník príspevku prednesených na XXIX. Celostátní Konferenci Archeologu Stredoveku Ceské Republiky a Slovenské Republiky k problematice archeologie stredovekých komunikací: Prachatice 6. - 10. Ríjna 1997, 1998)
Keywords: hradisko

Fondation d'une abbaye lorraine au XIIe siècle: l'exemple de Sainte-Marie-au-Bois - Collin, Hubert (Les Prémontrés et la Lorraine XIIe-XVIIIe siècle: 23e Colloque du Centre d'Etudes et de Recherches Prémontrées tenue à Pont-à-Mousson en octrobre 1997, 1998)
Keywords: sainte-marie-au-bois

De "Oude Molen" van Vossem - De Séjournet-Van Rijckevorsel, Marie-Elizabeth (De woonstede door de eeuwen heen: Tijdschrift van de Koninklijke Vereiniging der Historische Woosteden van België en van de Stichting Tot behouden van Particuliere Historische Bwtenplaatsen en de Nederlandse Kastelenstichting, 1998)
Surveys the history of the watermill originally belonging to the Premonstratensian Park Abbey at Leuven (Heverlee)
Keywords: park

Nécrologe, XIIe-XVIIIe: essai de restitution du nécrologe original - Ducoeur, Danièle (D. Ducoeur, 1998)
Keywords: la lucerne

Gemeente Grootegast : terreinen Klokkenstoel en Premonstratenzer klooster : archeologisch onderzoek - Exaltus, R.P. (RAAP Archeologisch Adviesbureau, 1998)
Keywords: kuzemer

Evolution au cours des siècles de la salle capitulaire de l'abbaye de Lieu-Restauré Bonneuil-en-Valois, Oise. - François, Jean-Luc (Pratique et sacré dans les espaces monastiques au Moyen Âge et à l'époque moderne: actes du colloque de Liessies-Maubeuge 26, 27 et 28 septembre 1997, 1998)
Keywords: lieu-restauré

Monastic Ruins at Annaghdown, Co. Galway - Goaley, Michael (Annaghdown Heritage Society, 1998)
Keywords: annaghdown

Tekstuitgave van de Bredase necrologia en obituaria. Begijnhof (1353) ca. 1500-1626, Norbertinessenklooster Sint-Catharinadal (1271-1960). Grote of OLV kerk: kanunniken en kapelanen (1303-1580) - Gooskens, Frans (DANS Data Station Social Sciences and Humanities, 1998)
Keywords: sint-catharinadal

Neue Ausgrabungen in der Prämonstratenserabtei Speinshart (Landkreis Neustadt a. d. Waldnaab, Oberpfalz) - Heidenreich, Anja; Sandor, Zsuzsanna (Das archäologische Jahr in Bayern, 1998)
Keywords: speinshart

Zur Geschichte des Klosters Meerholz - Hermann, Kurt (Mitteilungsblatt. Heimatstelle, Main-Kinzig. Beiträge zur Heimatgeschichte. Kreisausschuß des Main-Kinzig-Kreises, Amt für Bildung, Kultur und Sport, 1998)
Keywords: meerholz

Whithorn and St. Ninian: the excavation of a monastic town, 1984-91 - Hill, Peter H. (Sutton Publishing, 1998)
OCLC: 260042642
Keywords: whithorn

Klášter premonstrátu Teplá - Hlinomaz, Milan (Historický sborník Karlovarska, 1998)
Keywords: teplá

Foundations of monasteries by members of the twelfth-century Polish nobility: a selection of cases - Jamroziak, Emilia (Annual of Medieval Studies at CEU, 1998)
Keywords: strzelno

Dla dobra konwentu i świeckich. Szkoły w norbertańskim opactwie św. Wincentego we Wrocławiu w okresie średniowiecza - Kaczmarek, Krzysztof (Nasza Przeszłość, 1998)
[Für das Wohl des Konvents und der Laien. Die Schulen in der Breslauer Prämonstratenser-Abtei St. Vinzenz im Mittelalter]
Keywords: wrocław

Die ehemalige Prämonstratenserinnenkirche in Enkenbach - Kaiser, Jürgen (850 Jahre Kloster Enkenbach 1148-1998, 1998)
Keywords: enkenbach

St. Martin in Zyfflich: Gründungs- und Ausbauphase eines niederrheinischen Stiftes im Mittelalter - Keppler, Frank (1998)
Keywords: zyfflich

The Steinfeld Cloister Glazing - King, David J. (Gesta, 1998)
The cloister of the Premonstratensian abbey of Steinfeld in the Eifel region in Germany was built in 1499-1517. Its twenty-seven windows were glazed with an extensive typological series, donor figures, and saints in two campaigns between ca. 1522 and 1558. On several occasions the glass was removed, carried away for protection against war damage, and then replaced. Finally, in 1802, through the efforts of John Christopher Hampp of Norwich, it was brought to England where it was sold and dispersed. Thirty-eight panels were acquired by Lord Brownlow and installed at Ashridge Park in the first half of the nineteenth century. These were later given to the Victoria and Albert Museum, London. Two other panels were identified in Bristol. All of this glass was extensively discussed in 1955 in a German publication which included a manuscript description of all the windows from 1719. This led to the identification of nearly ninety panels of Steinfeld glass in many locations, including collections in the U. S. A.; one panel sold at Sotheby's, London, was returned to Steinfeld. These newly identified panels have enabled the correction and refinement of earlier conclusions concerning the iconography and composition, although much further work remains to be done. An appendix lists all extant panels discovered to date.
Publisher: [University of Chicago Press, International Center of Medieval Art]
Keywords: steinfeld

Wirberg. Burg, Kloster, Pfarre - Köhler, Gustav Ernst (Heimatgeschichtliche Vereinigung Reiskirchen, 1998)
Keywords: wirberg

Die Prämonstratenser in Ungarn und ihre kulturellen Leistungen - Kovaćs, Andreas (Analecta Praemonstratensia, 1998)
Keywords: 🇭🇺 hungary (general)

Das Prämonstratenserinnenkloster Wülfersberg - Krings, Bruno (Gladbach früher und heute Festschrift aus Anlaß der 900-Jahr-Feier des Ortes, 1998)
Keywords: wülfersberg

Vom Schwesternkloster zum Chorherrenkonvent. Das Prämonstratenserkloster Enkenbach in der Pfalz - Krings, Bruno (850 Jahre Kloster Enkenbach: 1148-1998, 1998)
Keywords: enkenbach

Úcast bl. Hroznaty na krížových výpravách a založení kláštera Teplá. (Studie o životní etape ceského velmože na konci 12. století) - Kubín, Petr (Západoceský historický sborník, 1998)
Keywords: teplá; 👤 hroznata of bohemia

Provincie Fryslân: kloosterterrein te Lidlum, gemeente Franekeradeel : waarderend archeologisch onderzoek - Langen, G.J. de; Perger, T.M (RAAP Archeologisch Adviesbureau, 1998)
OCLC: 67519562
Keywords: lidlum

Die Grablege des Bremer Erzbischofs Gottfried von Arnsberg im Prämonstratenserstift St. Georg - Lüdecke, Torsten (Stadt Stade, 1998)
Keywords: stade

De vestiging van norbertijnenabijen in het graafschaap Vlaanderen (1129-1156) - Meijns, Brigitte (Jaarboek voor Middeleeuwse Geschiedenis, 1998)
The installation of Norbertine abbeys in the county of Flanders (1129-1156).
Keywords: 🇧🇪 belgium (general); 🇫🇷 france (general)

Baubegleitende archäologische Beobachtungen im Bereich des ehemaligen Prämonstratenserklosters in Gramzow, Landkreis Uckermark - Müller, H.H.; Walther, Eckhard; Fink, R. (Angermünder Heimatkalender, 1998)
Keywords: gramzow

Ehemaliges Prämonstratenser-Stift St. Peter und Paul Marchtal - Müller, Maximilian; Aßfalg, Winfried (Kath. Kirchengemeinde St. Peter und Paul, 1998)
Keywords: marchtal

Twelfth-century stained glass in Easby parish church, North Yorkshire - O'Connor, David (Medieval Art: Recent Perspectives. A Memorial Tribute to C.R. Dodwell, 1998)
Keywords: easby

Excavations at St Mary's Abbey, West Dereham, on the possible stable range at the former monastic guesthouse complex - Penn, Kenneth (1998)
Keywords: west dereham

De abten van Middelburg (1123-1574) - Polak, Menno Sander (Archief. Mededelingen van het Koninklijk Zeeuwsch Genootschap, 1998)
Keywords: middelburg

Želivský, Jan (Jan von Selau), radikaler hussitischer Prediger (um 1380-90 - 1422) - Polívka, Miloslav (Lexikon des Mittelalters, 1998)
Keywords: 👤 jan želivský

L'abbaye de la Sainte-Trinité de la Lucerne - Pougheol, Jacques; Lelégard, Marcel; Ducoeur, Danièle (Art de Basse-Normandie, 1998)
Keywords: la lucerne

Zacharias v. Besançon (Chrysopolitanus) OPraem, theologischer Schriftsteller (12. Jh.) - Prelog, Jan (Lexikon des Mittelalters, 1998)
Keywords: 👤 zachary of besançon

L'église Saint-Sulpice de Seraincourt - Rivière, Aimée (Mémoires de la Société historique et archéologique de Pontoise, du Val-d'Oise et du Vexin, 1998)
Keywords: seraincourt

Strata Florida Abbey, Talley Abbey - Robinson, David M.; Platt, Colin (Cadw Welsh Historic Monuments, 1998)
Keywords: talley

Kirchengründung, Patronatsaufteilung: das Kloster Meer und seine Grundherrschaft - Rotthoff, Guido (Krefeld : die Geschichte der Stadt: Von der Frühzeit bis zum Mittelalter, 1998)
Keywords: meer

Die Ausgrabungen 1992-1997 im Prämonstratenserkloster Speinshart, Lkr. Neustadt/Waldnaab - Sandor, Zsuzsanna; Heidenreich, Anja (Beiträge zur Archäologie in der Oberpfalz, 1998)
Keywords: speinshart

Les dimensions multiples du voir. Les rêves et l'image dans l'autobiographie de conversion d'Hermann le Juif au XIIe siècle - Schmitt, Jean-Claude (Micrologus: Natura, scienze e società medievali / Nature, Sciences and Medieval Societies, 1998)
Keywords: 👤 hermann of cologne

Dryburgh Abbey (Mertoun parish): Watching Brief - Sharman, P. (Discovery and Excavation in Scotland, 1998)
Keywords: dryburgh

Anselm, Bischof von Havelberg - Springer, Matthias (Persönlichkeiten der Geschichte Sachsen-Anhalts, 1998)
Keywords: 👤 anselm of havelberg

Klöster und Laien: Zisterziensisch-prämonstratensische Differenzen und ihre Wirkungen im 12. Jahrhundert - Staab, Franz (850 Jahre Kloster Enkenbach 1148-1998, 1998)
Keywords: 📚 premonstratensian (general)

Das nassauische Zollprivileg des Klosters Altenberg von 1252 für Herborn - Störkel, Rüdiger (Nassauische Annalen, 1998)
Keywords: altenberg

Excavación arqueológica en el Monasterio de Santa María de los Huertos (Segovia) - STRATO Arqueologia (Servicio Territorial de Cultura de la Junta de Castilla y León en Segovia, 1998)
Keywords: santa maria de los huertos

Charles-Louis Hugo, abbé d'Étival, historiographe de la Lorraine - Taillard, Monique (Les Prémontrés et la Lorraine: XIIe-XVIIIe siècle, 1998)
Keywords: étival

Die mittelalterliche Bibliothek der Abtei Weißenau - Wenzel, Elke (Peter Lang, 1998)
Keywords: weissenau

Het Monnikenspoor: Op zoek naar middeleeuws Overijssel, van Vollenhove aan de Zuiderzeekust tot Clarholz in Westfalen - Wiedijk, Frederik M.; Wiersma, F.A. (Stichting Stimuland Overijssel, 1998)
Keywords: clarholz; vollenhove

Ruine als reizvolle Topographie: Kommunale Begegnungsstätte in der Martinskirche in Zülpich - Winkler, Olaf (Bauwelt, 1998)
Keywords: zülpich

Noble pursuits: Family, power, and gender in the Premonstratensian monasteries of northwestern Germany, 1120-1250 - Wolbrink, Shelley Amiste (University of Cincinnati, 1998)
Keywords: 🇩🇪 germany (general)

Vom Ort der Besinnung zur Stätte der Begegnung: Zülpich, "Martinskirche" - Zanger, Octavia (Denkmalpflege im Rheinland, 1998)
Keywords: zülpich